(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
In progress modern intervention in radiology fluoroscopy biophysicist basics , image quality increase and radiation dose optimization strategies analysis does . In the study X-ray radiation physicist principles , image harvest to be mechanisms and dose reduce according to practical approaches seeing The purpose is diagnostic . accuracy and patient safety between balance provider scientific the basics presented to be